Angiotensin Type 2 Receptor Agonist C21 Ameliorates the High-Fat Diet–Induced Pancreatic β-Cell Dysfunction Partially by Activation of Antiapoptosis and Autophagy. Issue 2 (February 2019) - Liu, Min; Li, Xiaojing; Ha, Si; Wang, Anping; Yin, Shinan; Mu, Yiming
Abstract : Objective: We aim to investigate whether C21, a selective angiotensin type 2 receptor agonist, can exert protective effects on pancreatic β-cells through activation of antiapoptosis and autophagy. Methods: The high-fat diet–induced obese rats (HFDs) were under C21 treatment for 4 weeks. Results: C21 treatment decreased the fasting glucose levels and improved β-cell insulin secretory function in the HFD group. Hematoxylin and eosin staining and electron microscopy indicated that the islet morphology was improved in the C21-treated obese rats, which was associated with increased levels of the key transcription factor PDX1, glucose sensing, and uptaking protein GCK and GLUT2, respectively. C21 treatment exerted antiapoptotic effects through decreasing the levels of apoptotic marker Caspase-3 while increasing the levels of antiapoptotic markers AKT, p-AKT, and BCL2. C21 treatment also induced autophagosome formation in the mitochondria of the β-cells in the HFD group accompanied by increased levels of autophagy markers, LC-3B and Beclin-1. Conclusions: The results suggested C21 treatment decreased the fasting glucose level and protected β-cell function in the HFD-induced obese rat model, which in part through activation of antiapoptotic and autophagy processes. This study provided preclinical evidence for the utilization of C21 in the treatment of type 2 diabetes.